New Transposon Tools Tailored for Metabolic Engineering of Gram-Negative Microbial Cell Factories - Martínez-García, Esteban; Aparicio, Tomás; de Lorenzo, Víctor; Nikel, Pablo I. (Frontiers in Bioengineering and Biotechnology, 2014)
Re-programming microorganisms to modify their existing functions and/or to bestow bacteria with entirely new-to-Nature tasks have largely relied so far on specialized molecular biology tools. Such endeavors are not only relevant in the burgeoning metabolic engineering arena, but also instrumental to explore the functioning of complex regulatory networks from a fundamental point of view. À la carte modification of bacterial genomes thus calls for novel tools to make genetic manipulations easier. We propose the use of a series of new broad-host-range mini-Tn5 vectors, termed pBAMDs, for the delivery of gene(s) into the chromosome of Gram-negative bacteria and for generating saturated mutagenesis libraries in gene function studies. These delivery vectors endow the user with the possibility of easy cloning and subsequent insertion of functional cargoes with three different antibiotic resistance markers (kanamycin, streptomycin, and gentamicin). After validating the pBAMD vectors in the environmental bacterium Pseudomonas putida KT2440, their use was also illustrated by inserting the entire poly(3-hydroxybutyrate) (PHB) synthesis pathway from Cupriavidus necator in the chromosome of a phosphotransacetylase mutant of Escherichia coli. PHB is a completely biodegradable polyester with a number of industrial applications that make it attractive as a potential replacement of oil-based plastics. The non-selective nature of chromosomal insertions of the biosynthetic genes was evidenced by a large landscape of PHB synthesis levels in independent clones. One clone was selected and further characterized as a microbial cell factory for PHB accumulation, and it achieved polymer accumulation levels comparable to those of a plasmid-bearing recombinant. Taken together, our results demonstrate that the new mini-Tn5 vectors can be used to confer interesting phenotypes in Gram-negative bacteria that would be very difficult to engineer through direct manipulation of the structural genes.